2015
DOI: 10.18632/oncotarget.3426
|View full text |Cite
|
Sign up to set email alerts
|

FTY720 enhances TRAIL-mediated apoptosis by up-regulating DR5 and down-regulating Mcl-1 in cancer cells

Abstract: FTY720, Fingolimod, is a functional antagonist to the sphingosine-1-phoaphate (S1P) receptor and an inhibitor of sphingosine kinase 1. Here, we showed that a combination of FTY720 and TRAIL induced apoptosis in human renal, breast, and colon carcinoma cells. Most importantly, this combination had no effect on normal cells. Furthermore, the combined treatment with FTY720 and TRAIL reduced tumor growth in xenograft models. FTY720 up-regulated death receptor (DR)5 at post-translational level. Knockdown of DR5 mar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 50 publications
0
16
0
Order By: Relevance
“…Studies from our group demonstrated that SPL expression is high in the intestinal epithelium but downregulated in murine adenomas and human colorectal cancers [ 11 , 61 ]. This finding, combined with a growing appreciation for the key role S1P signaling plays in colon cancer [ 156 159 ], prompted us to investigate the potential effect of gut epithelial SGPL1 disruption on the development of CAC. Toward that end, we generated an inducible intestinal epithelium-specific SPL KO mouse (SPL GutKO ) using Cre/lox technology [ 10 , 147 ].…”
Section: S1p Signaling and Inflammationmentioning
confidence: 99%
“…Studies from our group demonstrated that SPL expression is high in the intestinal epithelium but downregulated in murine adenomas and human colorectal cancers [ 11 , 61 ]. This finding, combined with a growing appreciation for the key role S1P signaling plays in colon cancer [ 156 159 ], prompted us to investigate the potential effect of gut epithelial SGPL1 disruption on the development of CAC. Toward that end, we generated an inducible intestinal epithelium-specific SPL KO mouse (SPL GutKO ) using Cre/lox technology [ 10 , 147 ].…”
Section: S1p Signaling and Inflammationmentioning
confidence: 99%
“…FTY720 is a synthetic compound produced by modification of a metabolite from I. sinclairii and has strong anti-cancer activity. For example, FTY720 induces cell death in multiple cancer cells [ 1 , 2 , 3 , 4 ] and sensitizes cancer cells to chemotherapy and radiotherapy [ 5 , 6 , 7 , 8 ]. Interestingly, FTY720 has also been seen to increase non-apoptotic cell death.…”
Section: Introductionmentioning
confidence: 99%
“…S1P is a bioactive lipid with oncogenic functions that promoting tumor cell growth and invasion. SphK1 has received increased attention during the past years [ 5 6 ]. SphK1 is overexpressed in various cancers, and the upregulation of SphK1 is associated with poor prognosis in many types of human cancers.…”
Section: Introductionmentioning
confidence: 99%